2021
DOI: 10.29333/iejme/10891
|View full text |Cite
|
Sign up to set email alerts
|

Concept Formation Processes regarding Height and Base in Triangles

Abstract: The paper addresses concept formation processes of a student in the field of geometry. More precisely, the paper deals with the question of how to assist a student in a mathematical concept formation process -in the context of area calculations in triangles -with a specially designed learning environment based on the usage of 3D printed objects. Methodologically, we use the descriptive framework of the concept of Domains of Subjective Experience for the analysis of our case study. The objective is to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Anna takes a ruler, paper and pencil and starts drawing her triangle. Anna draws a triangle (Figure 2) with one side of the triangle parallel to the edge of the leaf (see also Pielsticker, 2021).…”
Section: Analysis and Results -Case Study In Empirical Contexts Trian...mentioning
confidence: 99%
See 1 more Smart Citation
“…Anna takes a ruler, paper and pencil and starts drawing her triangle. Anna draws a triangle (Figure 2) with one side of the triangle parallel to the edge of the leaf (see also Pielsticker, 2021).…”
Section: Analysis and Results -Case Study In Empirical Contexts Trian...mentioning
confidence: 99%
“…with issues relating to 3D printing, 3D pen or dynamic geometry software (DGS) (for example GeoGebra) in mathematics lessons (e.g. Dilling & Witzke, 2020;Elschenbroich, 2018;Elschenbroich & Seebach, 2018;Kaenders & Schmidt, 2014;Ng, 2017;Ng et al, 2018;Panorkou & Pratt, 2016;Pielsticker, 2021). Thus, manipulatives that relate to this world are an essential element of teaching practice, as they can motivate, illustrate and justify mathematical relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other programs of this type, Tinkercad includes a particularly intuitive approach to directly modeling three-dimensional (3D) objects and provides easy access to such software for first-time users such as primary school students. As several research projects have already shown, this program provides students of all ages with a good start in 3D printing technology (Dilling & Vogler, 2021; Ng et al, 2018; Pielsticker, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%